Lactic Fermentation of Cereal Flour: Feasibility Tests on Rice, Oat and Wheat - Gallo, Marianna; Nigro, Federica; Passannanti, Francesca; Salameh, Dana; Schiattarella, Paola; Budelli, Andrea; Nigro, Roberto (Applied Food Biotechnology, 2019)
Background and objective: Consumers show increasing interests in probiotic foods and lactic acid fermentations. Cereal flour, can be a good fermentable substrate due to its prebiotic nature; from which, synbiotic products can be prepared. The aim of the current study was to investigate if three various cereal flours rice, oat and wheat would be good potentially functional foods. Material and methods: Fermentation tests were carried out on rice, oat and wheat flours, using Lactobacillus paracasei CBA L74 and 1.5-L fermenter with 1-L working volume. After 24 h, microbial growth, pH value, lactic acid production and starch consumption were assessed. Results and conclusion: In all three flours, pH reduction was seen; particularly in rice flour. The highest Lactobacillus growth and lactic acid production were achieved at the end of rice fermentation. The greatest starch consumption was reported at the end of rice fermentation. In conclusion, lactic fermentation of cereals as potentially functional foods was possible for the three flours. However, the best result belonged to rice flour. Conflict of interest: The authors declare no conflict of interest.